Pengaruh Cash Holding, Ukuran Perusahaan, Nilai Perusahaan Dan Kualitas Audit Terhadap Praktik Perataan Laba - Aditya Gunawan; Slamet Wiyono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study refers to problems related to income smoothing practices which are influenced by various factors. In this case, it is interesting for the researcher to conduct another study related to the problem of income smoothing practices. This study aims to determine whether there is a relationship between Cash Holding, firm size, Firm Value and audit quality on income smoothing practices. The analytical method used by the researcher is a logistic analysis method with purposive sampling technique and the data used are annual report data and financial reports for manufacturing companies in the consumer non-cyclicals listed on the Indonesian Stock Exchange (IDX) for the 2018-2022 period. From the results of the research that has been done, it shows that Cash Holding variables, firm size, Firm Value and audit quality have a positive effect on income smoothing practices.